Knowledge, networks and space: connectivity and the problem of non-interactive learning - Glückler, Johannes (Regional studies, 2013)
Glückler J. Knowledge, networks and space: connectivity and the problem of non-interactive learning, Regional Studies. This paper develops an integrative perspective of network theory and economic geography to attain a more inclusive understanding of the creation and reproduction of knowledge. A sympathetic review of network research in the social sciences conveys that geography is often a marginalized factor and that the empirical evidence about its effect on networks and knowledge has been ambiguous. The paper criticizes network theory for its tendency to overlook processes of collective learning that happen outside networks. By conceptualizing non-interactive learning, it posits that an inclusive theory of knowledge has to integrate network accounts of interactions and geographical accounts of non-interactive learning. Glückler J. 知识、网络与空间：连结性与非互动式学习的问题，区域研究。本文致力于发展网络理论与经济地理的整合性视角，以对知识的生产及创造做出更具包容性的理解。对于社会科学中网络研究的同情性回顾，传达了地理经常是被边缘化的因素，而地理对网络及知识所产生的影响之经验证据亦相当模煳。本文批判网络理论，因其有着忽略网络之外集体学习过程的倾向。透过概念化非互动式学习，本文假定知识的包容性理论必须整合对于互动的网络解释以及非互动式学习的地理解释。 网络理论emsp;知识emsp;创新emsp;非互动式学习emsp;社会网络分析emsp; Glückler J. Les connaissances, les réseaux et l'espace: la connectivité et le problème de l'apprentissage non interactif, Regional Studies. Cet article cherche à développer un point de vue intégré de la théorie des réseaux et de la géographie économique afin d'arriver à comprendre la production et la reproduction des connaissances. Un compte rendu favorable de la recherche en réseau dans les sciences sociales démontre que souvent la géographie est un facteur marginalisé et que les preuves empiriques de son impact sur les réseaux et les connaissances s'avèrent ambigues. Cet article critique la théorie des réseaux pour sa tendance à perdre de vue les processus d'apprentissage collectif qui ont lieu au-delà des réseaux. En conceptualisant l'apprentissage non interactif, on pose comme postulat qu'une théorie inclusive de l'apprentissage doit intégrer des comptes de réseaux des interactions et des comptes géographiques de l'apprentissage non interactif. Théorie des réseauxemsp;Connaissancesemsp;Innovationemsp;Apprentissage non interactifemsp;Analyse des réseaux sociaux Glückler J. Wissen, Netzwerke und Raum: Konnektivität und das Problem des nicht-interaktiven Lernens, Regional Studies. In diesem Beitrag wird eine integrative Perspektive der Netzwerktheorie und Wirtschaftsgeografie entwickelt, um ein umfassenderes Verständnis der Erzeugung und Reproduktion von Wissen aufzubauen. Aus einer wohlwollenden Würdigung der Netzwerkforschung in den Sozialwissenschaften geht hervor, dass es sich bei der Geografie oft um einen marginalisierten Faktor handelt und dass die empirischen Belege über ihre Auswirkung auf Netzwerke und Wissen bisher mehrdeutig ausgefallen sind. In diesem Beitrag wird die Netzwerktheorie wegen ihrer Tendenz kritisiert, außerhalb von Netzwerken ablaufende Prozesse des kollektiven Lernens zu übersehen. Durch eine Konzeptualisierung des nicht-interaktiven Lernens wird die These aufgestellt, dass eine integrative Theorie des Wissens die netzwerkbezogene Darstellung von Wechselwirkungen mit der geografischen Darstellung von nicht-interaktivem Lernen kombinieren muss. Netzwerktheorieemsp;Wissenemsp;Innovationemsp;Nicht-interaktives Lernenemsp;Soziale Netzwerkanalyse Glückler J. Conocimiento, redes y espacio: conectividad y el problema del aprendizaje no interactivo, Regional Studies. En este artículo se desarrolla una perspectiva integradora de la teoría de redes y la geografía económica para llegar a entender de forma cabal la creación y reproducción del conocimiento. A partir de una revisión favorable de los estudios de las redes en las ciencias sociales se deduce que la geografía es muchas veces un factor marginado y que la evidencia empírica sobre su efecto en las redes y el conocimiento ha sido ambigua. En este artículo se critica la teoría de las redes por su tendencia a ignorar los procesos del aprendizaje colectivo que ocurren fuera de las redes. Al conceptualizar el aprendizaje no interactivo, se propone que una teoría integradora del conocimiento tiene que combinar la presentación de las interacciones en las redes con la presentación geográfica del aprendizaje no interactivo. Teoría de redesemsp;Conocimientoemsp;Innovaciónemsp;Aprendizaje no interactivoemsp;Análisis de redes sociales